Program Mitigasi Bencana Banjir dan Tanah Longsor Akibat Cuaca Ekstrim di Desa Sade Lombok Tengah NTB - Made Sutha Yadnya; L.A.S. Irfan Akbar; Abdulah Zainuddin; Bulkis Kanata; Teti Zubaidah; Paniran Paniran (Universitas Mataram, 2021)
The condition of the situation in Sade Village is a hill, slope and mountainous area with and has a marble of more than 20 degrees, a thick layer of soil above the hillside, there is a poor water and land use system, resulting in flooding and landslides. The incident occurred in early 2021. This was carried out by a community service program to anticipate the possibility of floods and landslides due to extreme weather. This service was carried out by the Research Group on Electro Magnetic Technology and Environmental Conservation for Humanity. One of the missions related to the village community is towards Tangguh Bencara Village (DESTANA).